2008
DOI: 10.1002/sce.20296
|View full text |Cite
|
Sign up to set email alerts
|

Finding pearls: Psychometric reevaluation of the Simpson–Troost Attitude Questionnaire (STAQ)

Abstract: ABSTRACT:The Simpson-Troost Attitude Questionnaire (STAQ) was developed as part of a study to assess adolescent commitment to and achievement in science. For this psychometric reappraisal of the 57-item STAQ, data were analyzed from a convenience sample of 1,754 secondary students. Confirmatory and exploratory factor analyses were applied, and results suggested that the STAQ can be shortened from 57 to 22 items spanning five

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
1
30
1
1
Order By: Relevance
“…STAQ-revised is a revised form of Simpson-Troost attitude questionnaire that was developed by Owen et al (2008) to assess adolescent commitment to and achievement in science. STAQ has 22 Likert items that examines attitude towards science but we added 8 items to it regarding cultural and ethical properties of our country Iran.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAQ-revised is a revised form of Simpson-Troost attitude questionnaire that was developed by Owen et al (2008) to assess adolescent commitment to and achievement in science. STAQ has 22 Likert items that examines attitude towards science but we added 8 items to it regarding cultural and ethical properties of our country Iran.…”
Section: Methodsmentioning
confidence: 99%
“…Since student attitudes toward science effect course and career choices, measuring the impact of reform efforts on student attitudes is important and will require measurement tools with robust psychometric properties (Owen et al, 2008). Attitudinal studies in science education area are mostly pertinent to elementary, middle and high school students', and in some cases college students' attitudes towards science (Turkmen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Toliau metodo analizės strategija pasirinkta, atsižvelgiant į literatūroje aprašytas skalių pakartotinio vertinimo ir tikslinimo procedūras (Owen et al, 2008;Valickas, Želvienė ir Grakauskas, 2010;Thompson, 2005). Bendroji pirmojo tyrimo imtis (740 dalyvių) atsitiktiniu būdu padalyta į dvi grupes maždaug po 50 proc.…”
Section: Pirmojo Tyrimo Rezultataiunclassified
“…According to De Jong (2007), there were three main waves of science education reform. A shift in the direction of science education began in the late 1950s, where the nation, after much inquiry, determined that neighboring countries had a more prolific understanding of science content and curriculum (De Jong, 2007;Owen et al, 2008). In the 1980s came the second wave of reform in science education.…”
Section: Trends In Science Educationmentioning
confidence: 99%
“…The survey used in this student only 7 questions from the original Attitude Towards Science Survey as these questions pertained specifically to students attitude toward science, while other questions focused on parents attitude, teachers attitude, and overall valuing of science. These same questions were utilized in a subsequent study that reported a coefficient alpha of 0.88 (Owen et al, 2008).…”
Section: Instrumentationmentioning
confidence: 99%